Nanocube In2O3@RGO heterostructure based gas sensor for acetone and formaldehyde detection. Issue 61 (8th August 2017) - Mishra, Rajneesh Kumar; Murali, G.; Kim, Tae-Hyung; Kim, Jee Hun; Lim, Young Jin; Kim, Byoung-Suhk; Sahay, P. P.; Lee, Seung Hee
Abstract : Here, we demonstrated the formation of active sites O2 − and O − on the surface of nanocube In2 O3 @RGO heterostructure, gas sensing mechanisms and fluctuations in potential barrier height before and after insertion of acetone and formaldehyde. Abstract : Here, we studied the gas sensing response properties for acetone and formaldehyde by a chemiresistive nanocube In2 O3 @RGO heterostructure sensor. The nanocube In2 O3 @RGO heterostructure based sensor demonstrates a high response to acetone (∼85%) and formaldehyde (∼88%) at 25 ppm concentration and optimum working temperatures of 175 °C and 225 °C, respectively. Additionally, we examined the influence of potential barrier heights in the response/recovery time of the nanocube In2 O3 @RGO heterostructure based acetone and formaldehyde gas sensor. The real-time response/recovery analysis reveal that the sensor response depends on the potential barrier height as well as adsorbed active sites (O2 − & O − ) on the sensor surface. Furthermore, the nanocube In2 O3 @RGO heterostructure based gas sensor shows good selectivity to acetone and formaldehyde at optimum working temperature of 175 °C and 225 °C, respectively, compared to the other interfering gases such as ethanol, methanol, chloroform, toluene, benzene, ammonia, formic acid and acetic acid. The life-time analysis has been performed for 30 days, which showes the stability of nanocube In2 O3 @RGO heterostructure based acetone and formaldehyde sensor.